2016
DOI: 10.1016/j.aap.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of personality traits on distracted driving behaviors in teens and older adults

Abstract: Objective To determine the impact of personality on distracted driving behaviors. Method Participants included 120 drivers (48 teens, 72 older adults) who completed the 45-item Big Five Personality questionnaire assessing self-reported personality factors and the Questionnaire Assessing Distracted Driving (QUADD) assessing the frequency of distracted driving behaviors. Associations for all five personality traits with each outcome (e.g. number of times texting on the phone, talking on the phone, and interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
2
18
2
Order By: Relevance
“…More broadly, our findings are consistent with research investigating the association between personality and risky driving behavior. We must note that these findings, in part, run contrary to those observed in the only other study to our knowledge that specifically examined personality correlates of distracted driving . Parr et al .…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…More broadly, our findings are consistent with research investigating the association between personality and risky driving behavior. We must note that these findings, in part, run contrary to those observed in the only other study to our knowledge that specifically examined personality correlates of distracted driving . Parr et al .…”
Section: Discussioncontrasting
confidence: 94%
“…In a small sample ( n = 120), Parr et al . found that younger ( n = 48) and older drivers ( n = 72) differed with respect to the associations between personality traits and distracted driving tendencies . Whereas only greater extraversion was associated with distracted driving behaviors in adults, greater openness and lower agreeableness were associated with increased distracted driving tendencies in teenage drivers.…”
Section: Introductionmentioning
confidence: 92%
“…Notably, age was a significant predictor of distracted driving, in that older age was predictive of lower engagement in distracted driving behaviors. Similarly, Parr et al (2016) found the same relation between age and engagement in cellular distraction while driving, with adolescents reporting more engagement with using the phone and texting while driving than older adults, but no difference between age groups for having a cell phone conversation while driving. These studies conclude that distracted driving is a phenomenon not only seen with young drivers, but also in older and more experienced drivers, just not as frequently.…”
Section: Introductionmentioning
confidence: 65%
“…Although the focus of this review is what goes awry visually and cognitively when children and adolescents use mobile technology in traffic environments, social aspects of distracted behavior cannot be ignored. These aspects include personality and its influence on behavior (Parr et al., ), but most prominently involves youth peer relations. Youth often recognize the dangers of distracted behavior in transportation contexts yet still engage in it (McDonald & Sommers, ); empirical research in other fields (e.g., substance use, sexual risk taking) offers parallels and perhaps prevention strategies.…”
Section: Discussionmentioning
confidence: 99%